Application of flexible working arrangement and the implacation towards organizational commitment at principle asset management penang branch / Noor Zarifah Izzati Mustafa Kamil - Mustafa Kamil, Noor Zarifah Izzati (2019)
Today, consultants of Principal Asset Management Penang Branch are facing low rate of organizational commitment even flexible working arrangement has been applied to their working culture. Hence, the objectives are to identify the effect of flexitime, teleworking and job sharing as well as gender differences towards organizational commitment. The research methodology for this study is using random sampling technique. Data obtained from 119 respondents from Principal Asset Management Penang Branch. Result shows that job sharing was significantly explained by the organizational commitment and another two variables which are flexitime, teleworking and gender differences were not significantly explained by organizational commitment. Therefore, this study has a few recommendation for organization and future researcher. The organization need to increase awareness regarding the application of flexible working arrangement in performing job among consultants. Meanwhile, the future researcher is needed for continues studies in other geographical location due to very small population. In addition, other variables that enable to improve organizational commitment also needed for future research.